Cow management modulates gene expression in the mammary gland, a possible epigenetics role - Gigli, Isabel; Maizon, Daniel Omar (2017)
Epigenetics, the study of the change in gene expression that occurs without alteration in DNA sequences, leads to modifications that can be passed on by mitosis. It has been known for many years that cow management during lactation affects milk production. Now it is clear that some factors influence milk production even before the onset of lactation (during the dry period). In the last decade, a greater understanding of the molecular events that occur in the mammary epithelial cells provided an explanation for these changes. Gene expression in the mammary gland shows a temporal–spatial regulation. This is achieved by different regulatory layers of gene expression involving, for example, chromatin condensation and the combinations of several hormones and transcription factors. The goal of this review is to bring together an update of studies on gene expression in the mammary gland, highlighting the possible influence of cow management on epigenetic mechanisms. The impacts of milking frequency, mastitis, photoperiod and heat stress on gene expression and their effects on milk production were discussed. Understanding how the mammary gland responds to external factors will help to design better strategies and technologies to enhance milk production.